PRODUCERS EDUCATION ABOUT MICROBIOLOGICAL INOCULATES APPLICATION IN FUNCTION OF SOIL FERTILITY - Milošević, Nada; Potrebic, Velibor; Arsenijević, Željko (Economics of Agriculture, 2018)
Soil protection against degradation in agricultural production is one of the measurements in the frame of aims and guidelines of integral and organic production. Because of that, there are more and more researches which are directed toward finding the alternative - organic ways in soil fertilization, in the aim of undesirable effects avoiding. Application of microbiological inoculates with nitrogen fixing bacteria with the purpose of soil fertilization, replaces or refill nitrogen mineral fertilizers. Decrement of mineral fertilizers quantities complies with integral agricultural production concept, what represent important step to organic agriculture. Appliance of these new methods requests constant use of available knowledge through education of direct producers. Awareness and habits of producers have to be changed in the direction of multifunctional agriculture and rural development, with spreading of knowledge of soil fertility maintaining by the appliance of all bio-agro-technical measurements. By inoculates appliance in maize, wheat and soy bean production with certain groups of nitrogen fixing bacteria, soil biogenity is being preserved and maintained, plants needs for necessary assimilations nutrients are being satisfied, phytoparasites control is secured, healthy food is produced, what satisfied all ecological and economic criterions of viable system.